Identity ambivalences of the Eurasian Macanese : historical dynamics, political regimes and food practices - Gaspar, Marisa C. (2021)
This article focuses on the phenomenological experience of identity ambivalence arising from the Eurasian Macanese community through their phenomenological experience of identity ambivalence. Our thematic framework includes the structural impact of colonial and post colonial political regimes in Macao, historical influences on contemporary identity and sociocultural expressions of creolisation. It is argued that the Macanese people illustrate the memory of the ambivalent encounter between the two extremities of the Eurasia (China and Portugal) which started in the 16th-c. and never ceased moving forces to the present day. Furthermore, in the context of fieldwork with the Macanese community in Portugal, an ethnographic approach helps reveal the ambivalent dynamics of similarities and differentiation with respect to food practices and commensality as expressed over dinner by a group of close friends in Lisbon.